1999
DOI: 10.4269/ajtmh.1999.60.674
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to Plasmodium falciparum major surface antigens and their relationship to human activities associated with malaria transmission.

Abstract: Abstract. In Brazil, two types of activities have led to the worsening of malarial transmission in the Amazon region: prospecting/mining and agricultural settlements. In the present study, we analyze the cellular response of 52 of these individuals (14 gold-miners and 38 farmers) living within the same endemic area. Two Plasmodium falciparum major surface antigens (recombinant proteins) were used for cellular proliferative assays: circumsporozoite protein and merozoite surface protein-1. The frequency of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…2011). Overall, these data corroborate earlier studies, concluding that malaria transmission is a local problem, which varies within a village according to the microepidemiological factors (Carvalho et al. 1999; da Silva‐Nunes et al.…”
Section: Discussionsupporting
confidence: 91%
“…2011). Overall, these data corroborate earlier studies, concluding that malaria transmission is a local problem, which varies within a village according to the microepidemiological factors (Carvalho et al. 1999; da Silva‐Nunes et al.…”
Section: Discussionsupporting
confidence: 91%
“…11,15 Cells from adults who reported less than five years of malaria exposure in Brazilian endemic areas also had a significant proliferative response to CS proteins. 7,8,16 The high frequency of proliferative response now observed in the CB group is consistent with those earlier studies. However, a low level of in vitro cellular proliferative response to CS proteins in subjects continuously exposed to P. falciparum and P. vivax transmission for at least 10 years (Terra Nova do Norte group) is reported for the first time in Brazil.…”
Section: Discussionsupporting
confidence: 81%
“…For example, gold mining is the predominant activity in the riverine Jacareacanga. It was previously shown that mining populations exhibit acquisition of immunity to malaria [43]. Mining can also contribute to an increase in number of mosquito breeding sites due to extensive borrow pits dug along mining sites, mimicking the riverine floodwater impoundments [9].…”
Section: Discussionmentioning
confidence: 99%